Kritik Sosial dalam Novel Entrok Karya Okky Madasari: Kajian Sosiologi Karya Sastra - Indah Fitri Yulianti (LPPM STKIP PGRI Bandar Lampung, 2023)
This article discusses the social problems that occur in a literary work, namely the novel Entrok by Okky Madasari so that the emergence of an interesting social criticism to study. In the study of the sociology of literature, Soekanto and Sulistyowati revealed that there are nine types of social criticism, including 1) poverty, 2) crime, 3) family disorganization, 4) the problem of the younger generation in modern society, 5) war, 6) violation of norms. society, 7) population, 8) environment, and 9) bureaucracy. The theory is used as a reference to analyze the social criticism that exists in the Entrok novel because it is felt that there are many things that are relevant to the theory and many problems are quite complex in society at that time. This study uses qualitative research methods by applying literature studies as a source of research findings. After that the object is studied based on the theory of sociology of literature focused on social criticism to get a conclusion in the results of the study. The purpose of this research is to find out a social critique of a society's life in a literary novel which can later be used as a comparison in other literary works related to the theory of literary social criticism.